Lung clearance index and steroid response in pediatric severe asthma. Issue 4 (6th February 2020) - Irving, Samantha; Fleming, Louise; Ahmad, Fatima; Biggart, Elizabeth; Bingham, Yvvone; Cook, James; Hall, Pippa; Jamalzadeh, Angela; Nagakumar, Prasad; Bossley, Cara; Gupta, Atul; Macleod, Kenneth; et al.
Abstract: Introduction: Lung clearance index (LCI) is a measure of airway disease that has been shown to be abnormal in asthma. We hypothesized that LCI would be higher (worse) in children with severe therapy‐resistant asthma (STRA) compared with difficult asthma (DA) and healthy controls and that LCI would fall in response to parenteral steroids in STRA. Methods: Sixty‐four children with asthma who were prescribed high‐dose asthma therapy (GINA steps 4 or 5) performed LCI and spirometry. Forty‐three had STRA and 21 DA. Thirty‐nine of forty‐three STRA patients attended for a clinically indicated bronchoscopy during which an intramuscular injection of triamcinolone was given. LCI, spirometry, and fractional exhaled nitric oxide (FeNO) were performed on the day of the bronchoscopy and repeated 4 weeks later. Results: LCI was more abnormal in STRA (median: 7.40, range: 5.58‐12.34) than in DA (6.55, 5.77‐7.75), P  = .0006, and healthy controls (6.53, 5.57‐7.35), P  = .005. In contrast to the first second forced expired volume (FEV1 ), LCI improved following systemic steroids; of 20 STRA patients with an abnormal LCI at baseline, 13 improved following triamcinolone. LCI and FeNO responses were concordant. Conclusions: There is a subgroup of children with STRA in whom LCI is elevated who improve following parenteral steroids. LCI may be a valuable additional domain in assessing steroid response in pediatric asthma.